PROSES ISLAMISASI MELALUI DAKWAH DI SULAWESI SELATAN DALAM TINJAUAN SEJARAH - Dahlan, Muhammad (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
This paper break down the process of Islamization in South Sulawesi and propaganda methods adopted in the process. By using an approach based on historical analysis, this paper concludes that, the process of Islamization in South Sulawesi through several stages, the arrival of Muslim traders as bearers of Islam in the 16th century, after the advent of Islam King of Gowa-Tallo in the 17th century, shipping army for kings to develop Islamic Bugis although initially rejected by the Bugis, continues with the arrival of Datuk Bandang ri, ri Tiro Datuk, Datuk Pattimang broadcast and Islam. Adopted the method of preaching Islam is spreading the teachings of Islam to synchronize between pangadereng so that the process of Islamization in South Sulawesi take place quickly.